Diagnosis and treatment of patients with IgA nephropathy in Japan - Yasuhiko Tomino (The Korean Society of Nephrology, 2016)
Chronic kidney disease (CKD) is a worldwide public health problem that affects millions of people from all racial and ethnic groups. Although CKD is not one specific disease, it is a comprehensive syndrome that includes IgA nephropathy. As reported by the Japanese Society of Nephrology, 13.0 million people have CKD. In Japan, major causes of end-stage kidney disease are type 2 diabetic nephropathy, chronic glomerulonephritis, especially IgA nephropathy, hypertensive nephrosclerosis, and polycystic kidney disease. IgA nephropathy is characterized by polymeric IgA1 with aberrant galactosylation (galactose-deficient IgA1) increased in the blood and deposited in the glomerular mesangial areas, as well as partially in the capillary walls. The tonsils are important as one of the responsible regions in this disease. The clarification of the mechanism of galactose-deficient IgA1 production will pave the way for the development of novel therapies. The results of future research are eagerly awaited. At present, the most important therapeutic goals in patients with IgA nephropathy are the control of hypertension, the decrease of urinary protein excretion, and the inhibition of progression to end-stage kidney disease. Several investigators have reported that renin-angiotensin-aldosterone system inhibitors reduce levels of urinary protein excretion and preserve renal function in patients with IgA nephropathy. In Japan, tonsillectomy and steroid pulse therapy are more effective for patients with IgA nephropathy.